Side bias : a neuropsychological perspective - Mandal, Manas K.; Bulman-Fleming, M. Barbara; Tiwari, G. (Geetika) (Kluwer Academic Publishers, 2000)
`Rather than being an esoteric aspect of brain function, lateralization is a fundamental characteristic of the vertebrate brain essential to a broad range of neural and behavioral processes.' Professor Lesley J. Rogers, Chapter 1 of Side Bias: A Neuropsychological Perspective. This volume contains 14 chapters from a veritable `United Nations' of experts in the field of lateralization of function. They write comprehensive reviews, present data, and pose new questions concerning the evolutionary origins and development of side bias, methodological concerns with the way we measure handedness and footedness, and some more unusual aspects of human beings' lateralized behavior, such as asymmetrical cradling and pseudoneglect. The book will be essential reading for students of behavioral neuroscience and neuropsychology interested in lateralization of function as well as for established researchers in the field.